Digital nanoliter to milliliter flow rate sensor with in vivo demonstration for continuous sweat rate measurement. Issue 1 (7th December 2018) - Francis, Jessica; Stamper, Isaac; Heikenfeld, Jason; Gomez, Eliot F.
Abstract : A digital flowmetry sensor is fabricated with low limit of detection and wide dynamic range, that is suitable for lab-on-chip or wearable sweat sensing systems. Abstract : Microfluidic flow rate sensors have constraints in both detection limits and dynamic range, and are not often easily integrated into lab-on-chip or wearable sensing systems. We constructed a flow rate sensor that easily couples to the outlet of a microfluidic channel, and measures the flow rate by temporarily shorting periodic droplets generated between two electrodes. The device was tested in a dynamic range as low as 25 nL min −1 and as high as 900 000 nL min −1 (36 000× range). It was tested to continuously operate up to ∼200 hours. The device is also simple to fabricate, requiring inexpensive parts, and is small enough to be integrated into wearable devices. The required input pressure is as low as 370 Pascals. An ultra-low flow rate application was demonstrated for wearable sweat biosensing where sweat generation rates (nL min −1 per gland) were accurately measured in human subjects. The digital nanoliter device provides real-time flow rates for sweat rates and may have other applications for low flow rates in microfluidic devices.